KESIAPAN MENUJU PAUD RAMAH ANAK - Asep Deni Gustiana (Edutech, 2019)
The rise of acts of violence against children has become a problem that needs to be addressed by all elements, not only by parents, but teachers, schools, communities and other stakeholders are obliged to cooperate in protecting children. One of the government's efforts in dealing with these problems is by providing a child-friendly learning environment. Bandung City as a Child-Friendly City since 2016 should be a solution to providing a child-friendly environment. one of the indicators is having a child-friendly school. The child protection commission survey shows that more than 84% of cases of violence occur in schools, therefore the need and importance of child-friendly schools is a condition or indicator point of a child-worthy city precisely at cluster 4. To find out about the availability of child-friendly schools in Bandung Early Childhood Education Unit ECE in each District. The results of research in the field show that 52.9% of ECE units in Sukasari Sub-district are ready to become child-friendly ECE units, the remaining around 47.1% are not ready to become child-friendly ECE. This research is expected to be a material reflection for stakeholders in realizing child-friendly schools.